Bioavailability and Safety of the Factor Xa Inhibitor Edoxaban and the Effects of Quinidine in Healthy Subjects. Issue 4 (9th September 2013) - Matsushima, Nobuko; Lee, Frank; Sato, Toshiyuki; Weiss, Daniel; Mendell, Jeanne
Abstract Background Edoxaban is an oral, once‐daily, direct factor Xa inhibitor under investigation for stroke prevention in patients with atrial fibrillation and for treatment and secondary prevention of venous thromboembolism. This study evaluated edoxaban absolute bioavailability and effects of the P‐glycoprotein inhibitor quinidine on edoxaban pharmacokinetics after intravenous edoxaban administration. Methods Healthy volunteers received three treatments in a randomized sequence: single oral 60‐mg edoxaban dose, single intravenous 30‐mg edoxaban dose, and concomitant single intravenous 30‐mg edoxaban dose with quinidine 300 mg every 8 hours for 4 days. The primary objective was to determine absolute bioavailability of edoxaban. Secondary objectives included pharmacokinetics and pharmacodynamics of edoxaban after oral or intravenous administration, quinidine effect on intravenous edoxaban pharmacokinetics, and safety. Results Thirty‐six subjects were randomized; five discontinued (three for adverse events [AEs]). Edoxaban oral absolute bioavailability was 61.8%. With concomitant quinidine, total edoxaban exposure increased ∼35% and total clearance decreased ∼25%. Coagulation parameters increased after edoxaban administration in most subjects, but returned to baseline within 24 hours postdose. No deaths, serious AEs, or bleeding‐related AEs occurred. Conclusions Absolute bioavailability of edoxaban in healthy volunteers was established (61.8%). Edoxaban, administered orally or intravenously, appeared to be safe and well tolerated.